Growing Opportunities for Equitable, Interdisciplinary Undergraduate Food Systems Education: A Review of Food Systems Education at Land-Grant Institutions and Development of Open-Access Materials - Belarmino, Emily H.; Kolodinsky, Jane; Ammerman, Alice S.; Connor Volpe, Leah; Brown, Covington; Jilcott Pitts, Stephanie B.; Hanson, Karla L.; Sitaker, Marilyn; Wang, Weiwei; McGuirt, Jared T.; Carfagno, Michelle; Hunsinger, Emily; et al. (Frontiers in Sustainable Food Systems, 2022)
Post-secondary coursework related to agriculture and the food supply has been at the core of the United States' land-grant system for more than 150 years. However, as the complexity of food systems has grown, so too have critiques that the education provided in these programs is too narrow to adequately prepare graduates to address pressing food systems issues. In response, some higher education institutions have developed degrees in food systems. To support development of this burgeoning field, we created, tested, and refined four evidence-informed, interdisciplinary, equity-oriented, open-access teaching modules. These modules are based on our experience conducting a multi-site, multi-year transdisciplinary investigation of subsidized, or “cost-offset”, community supported agriculture and a survey asking instructors at land-grant institutions (n = 66) about topic offerings and current unmet needs for instructional materials. Our collaboration illuminated the potential and challenges of food systems research; underscored the value of transdisciplinary research teams; and identified several equity-oriented topics related to the design, implementation, and evaluation of local food initiatives suitable for advancing sustainable foods systems education. Instructors reported that the most helpful teaching aids would be case studies, lesson plans with active learning components, and reference lists with relevant peer-reviewed publications. The final modules seek to shed light on the complexity of food systems projects and build knowledge, vocabularies, and skills across disciplines engaged with food systems. Per instructor-defined needs, each module features a case study, active-learning activities, and references. We anticipate that the adaptable modules will be suitable for a wide range of students and courses.